Performing under pressure: Exploring the psychological state underlying clutch performance in sport? - Swann, C.; Crust, L.; Jackman, P.; Vella, S. A.; Allen, M. S.; Keegan, R. (Journal of Sports Sciences, 2017)
Clutch performance is improved performance under pressure. However, little research has examined the psychological state experienced by athletes in these situations. Therefore, this study qualitatively examined the subjective experience underlying clutch performance across a range of sports (e.g., team, individual) and standards (Olympic to recreational athletes). Sixteen athletes (Mage = 27.08 years; SD = 6.48) took part in in-depth, semi-structured interviews primarily after an exceptional performance (M = 4.38 days later; SD = 3.14). Data were analysed inductively and thematically. Clutch states involved 12 characteristics, including heightened and deliberate concentration, intense effort, and heightened awareness, which distinguished the experience of clutch from other optimal psychological states such as flow. Other characteristics, such as perceptions of control, were also reported and supported previous experimental research on clutch. These findings present in-depth qualitative insights into the psychological state underlying clutch performance, and are discussed in relation to the existing literature on optimal psychological states in sport.